Targeting α7 Nicotinic Acetylcholine Receptors in the Treatment of Schizophrenia - Hajos, Mihaly; Rogers, Bruce N. (Current Pharmaceutical Design, 2010)
The most abundant homomeric nicotinic acetylcholine receptors (nAChRs) in the mammalian brain are the pentameric α7 nAChRs which consist of five α7 subunits, and each subunit provides an orthosteric low affinity binding site for its endogenous ligand, acetylcholine. Distribution and high level expression of α7 nAChRs within the limbic circuitry, including the hippocampus and prefrontal cortical areas are in line with their involvement in various cognitive functions. Activation of α7 nAChRs generates a conformational change of sub-unit proteins, making the channel permeable to cations, in particular calcium, leading to change in neuronal activity and excitability, and via increased intracellular calcium, modulating transmitter release and neuronal network activity. Since genetic linkage studies implicated the α7 nAChRs subunit gene CHRNA7 in schizophrenia, there is a considerable interest for developing drug therapies targeting α7 nAChRs. In this review recent development of selective agonists and positive allosteric modulators of α7 nAChRs are discussed. In addition to summarizing medicinal chemistry efforts, both cellular and neuronal network pharmacology of α7 nAChRs are covered. The association between CHRNA7 gene and impaired P50 auditory gating has provided an attractive endophenotype, and its use as a potential translational biomarker for α7 nAChRs drug discovery is discussed. Preliminary clinical findings on α7 nAChRs agonists are also summarized.
Keywords: nicotinic